Technical analysis of the salary scale for public sector employees - R. S. Al-Madhidi, Raqeeb; L. Said, Abdul Salam (Journal of Economics and Administrative Sciences, 2021)
The research discusses the mechanism for analyzing the salary scale in the public sector through an analysis of grades, their stages, occupants and their financial entitlements, and the extent to which the information obtained for their investment in strategic planning, conducting correction and treatment can be used. The salaries of the employees in them, whose number is (1117) employees, to be a field of research, as the salary structure in it for the year 2019 was analyzed by relying on a number of statistical tools in the analysis process, including the arithmetic circles, upper limits, minimum limits and percentage, and with the help of the analysis tables forms approved by the researcher which Negative indicators appear, whether on the technical side of the administrative aspects of the salary scale, and then an analysis of the salary scale leads us to know the behaviours of the salary movement and its positioning, and a description of the technical and scientific description of the structure of job grades and their stages through different numbers and proportions resulting from the analysis process. The research concluded a set of conclusions, the most important of which is the knowledge of the technical and scientific description of the scale of career grades, their stages, occupants, distribution, concentration, and strategic impact, and the information generated by the analysis process from a future impression of the decision-maker. The state of net salaries and allowances, which are in the broader general, is not sufficient for workers to meet the requirements and burdens of life.